If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 5w + -15y + 5w + 10x + 7y = 0 Reorder the terms: 2w + 5w + 5w + 10x + -15y + 7y = 0 Combine like terms: 2w + 5w = 7w 7w + 5w + 10x + -15y + 7y = 0 Combine like terms: 7w + 5w = 12w 12w + 10x + -15y + 7y = 0 Combine like terms: -15y + 7y = -8y 12w + 10x + -8y = 0 Solving 12w + 10x + -8y = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-10x' to each side of the equation. 12w + 10x + -10x + -8y = 0 + -10x Combine like terms: 10x + -10x = 0 12w + 0 + -8y = 0 + -10x 12w + -8y = 0 + -10x Remove the zero: 12w + -8y = -10x Add '8y' to each side of the equation. 12w + -8y + 8y = -10x + 8y Combine like terms: -8y + 8y = 0 12w + 0 = -10x + 8y 12w = -10x + 8y Divide each side by '12'. w = -0.8333333333x + 0.6666666667y Simplifying w = -0.8333333333x + 0.6666666667y
| 4(8x-9)= | | 6x+40=15x-42 | | 2x^2-7=3x+4 | | -2y*2=0 | | (a)5w+3=4w+9 | | k+hj=6 | | 3-6x=11x-8x | | -2y*-y=0 | | 6a^2-30a+24= | | 2.7x+2.8=19 | | -17=3+5 | | 9x-12+2x=11x+6 | | d-2.94=1.36 | | 2(3x+4)-3=6x+5 | | -5+9=21 | | 3m-10=24m-5 | | x/18+x/3 | | 8(y+6)+y=4(y+5)+2 | | 1/31/2x/3 | | -4(3x-4)+1=-12x+17 | | 5x+4=12+5x | | 2x-3+4x-8=13 | | 5*29= | | 7x-8y=64 | | 11*15= | | 2(x-4)(x-3)=x-13 | | 9x+6=9(x-3) | | X+4/3=x-8/5 | | X/4-3=-4 | | -8-3+6*2= | | 3z=14-29 | | 3(3m-2)+10=3(m-4)-3 |